Literature Review: Pengaruh Pijat Oksitosin terhadap Involusi Uterus pada Ibu Postpartum: Literature Review: The effect of Oxytocin Massage on Uterine Involution in Postpartum Mothers - Siti Fatimah (Indonesian Journal of Midwifery (IJM), 2024)
The involution process during postpartum is a crucial physiological mechanism to avoid postpartum complications. One effort to support uterine involution is with oxytocin massage. There has been a lot of research on oxytocin massage but its effectiveness has not been studied in a wider environment. This study aims to examine articles on the effect of oxytocin massage on uterine involution in postpartum mothers. Researchers used three databases, namely Google Scholar, PubMed and Scopus. Full text, free articles published in the 2014-2024 range with keywords. The keywords used are “pijat oksitosin”, “involusi uterus”, “ibu nifas” in Indonesian. The keywords used in English are "oxytocin massage", "uterine involution", "postpartum". The author uses the PRISMA method and the quality of the articles uses JBI for later review. The results showed that 17 articles met the criteria and were included in the literature review. A total of 14 articles showed results supporting oxytocin massage as having a positive effect on uterine involution compared to controls. Meanwhile, 3 other articles stated there was no difference compared to the control. Measurement of uterine involution using uterine palpation. It can be concluded that oxytocin massage has a significant effect on uterine involution. It is recommended for health workers to teach families in oxytocin massage.   Abstrak Proses involusi pada postpartum merupakan mekanisme fisiologi krusial untuk menghindari komplikasi post partum. Salah satu upaya untuk mendukung involusi uteri adalah dengan pijat oksitosin. Telah banyak dilakukan penelitian pijat oksitosin namun belum dikaji tentang efektivitasnya pada lingkungan yang lebih luas. Penelitian ini bertujuan mengkaji artikel pengaruh pijat oksitosin terhadap involusi uterus pada ibu postpartum. Peneliti menggunakan tiga database yaitu google scholar, pubmed dan scopus. Artikel full teks, gratis yang terbit dalam rentang 2014-2024 dengan kata kunci Kata kunci yang digunakan adalah “pijat oksitosin”, “involusi uterus”, “ibu nifas” dalam Bahasa Indonesia. Kata kunci yang digunakan dalam Bahasa inggris adalah “oxytocin massage”, “uterine involution”, “postpartum”. Penulis menggunakan metode PRISMA dan kualitas artikel menggunakan JBI untuk kemudian di tinjau. Hasil didapatkan 17 artikel yang memenuhi kriteria dan dimasukkan dalam review literatur. Sebanyak 14 artikel yang menunjukkan hasil mendukung pijat oksitosin memberikan efek positif terhadap involusi uterus dibandingkan kontrol. Sedangkan 3artikel lainnya menyatakan tidak ada perbedaan dibandingkan dengan kontrolnya. Pengukuran involusi uteri menggunakan palpasi uterus. Dapat disimpulkan bahwa pijat oksitosin berpengaruh signifikan terhadap involusi uterus. Disarankan bagi tenaga kesehatan untuk mengajarkan keluarga dalam pijat oksitosin.